THE SPEECH ACTS IN ENGLISH FOR YOUNG LEARNERS CLASS DURING VIRTUAL INSTRUCTIONAL-PRACTICES - Sukmawati, Nur Najibah; Nasution, Sukma Septian; Taman, Purwanti; Astuti, Prihatin Puji (Universitas Pamulang, 2022)
Mode, as one of elements of context, can influence speech acts. Virtual meeting, as one of modes that signifies the absence of direct interaction potentially influences the speech acts too. This study aims at identifying speech acts in the instructional practices at selected elementary schools in South Tangerang, Banten to answer (1) what types of speech acts used by teachers and students of each school and (2) what factors influence the chosen speech acts. This is a content analysis that explores communication occurrences between teachers and young learners in English classes. Three pre-schools in Pamulang district were chosen as sources of data. The data were collected by recording their communication practices in three consecutive meetings. In total, there are nine communication practices from all the pre-schools. Then, the data were transcribed and segmented by clausal units to identify types of speech acts produced by each party. The findings show that every school performs similar patterns of speech acts dominated by the use of directive expression to maintain the students’ engagement, followed by declarative expression to stimulate the students’ active participation in various activities during the virtual instructional practices.